INTEGRAL POLICY FOR OVERCOMING CRIMINAL ACTS IN THE WATERS OF LAMPUNG PROVINCE - Maya Shafira; M Akib; FX Sumarja; Ahmad Irzal Fardiansyah (PT. Antis International Publisher, 2025)
Objective: This study aims to analyze various forms of criminal acts in the marine and fisheries sectors within Lampung waters and evaluate the implementation of integral policy responses to maintain maritime security and resource sustainability. Method: The research applies a multidisciplinary approach that includes legal, analytical, historical, case, and comparative methods. Additionally, field research and in-depth interviews with stakeholders from relevant institutions are conducted to support the findings with empirical data. Results: The study identifies multiple criminal activities, including fish bombing, illegal fishing, smuggling, narcotics trafficking, theft, oil and gas crimes, illegal mining, mismanagement, sexual offenses, possession of sharp weapons, and extortion. In response, two main policy strategies are implemented: non-penal (preventive) efforts—such as socio-economic development, legal awareness campaigns, moral education, and maritime patrols—and penal (repressive) efforts, emphasizing firm law enforcement to deter recidivism and reinforce legal compliance. Novelty: This study provides a comprehensive criminological analysis of maritime crimes specific to Lampung waters, integrating both preventive and repressive dimensions, and offers a model of integral policy implementation that balances social defense and welfare to strengthen maritime governance